Pengembangan Bahan Bimbingan Karir Berbasis Internet dalam Pelayanan Informasi Pada Siswa Kelas XI SMA - Rafael Lisinus Ginting; Tiur Elena Purba (INDONESIAN COUNSELING AND PSYCHOLOGY, 2021)
The purpose of this study was to develop internet-based career guidance materials in information services for class XI students at SMA Negeri 2 Medan. This career guidance material product allows students to be able to study independently and can fulfill the need for career information. The research method used is R&D research carried out by adapting the concept of research and development of the 4D (four-D) development model. The 4D development model consists of 4 main stages, namely: define, design, develop and disseminate. The data collection technique used a questionnaire consisting of media instruments, material instruments and user instruments, each of which was assessed by career material experts, media experts, and 34 students. XI and the effectiveness of internet-based career guidance materials for students